2015
DOI: 10.3389/fpsyg.2015.01759
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Memory for both Threat and Neutral Information Under Conditions of Intergroup Threat

Abstract: Few studies have examined the effect of intergroup threat on cognitive outcomes such as memory. Different theoretical perspectives can inform how intergroup threat should affect memory for threat-relevant and neutral information, such as the mood-congruency approach, Yerkes–Dodson law, Easterbrook’s theory, and also evolutionary perspectives. To test among these, we conducted two experiments to examine how exposure to intergroup threats affected memory compared to control conditions. In study 1, we manipulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Hence, these manipulations were perhaps not strong enough to facilitate postencoding biases, nor were they specifically matched to the encoded stimulus set (i.e., the stimuli were not normed to be amusing to match with the comedic clips). A similar concern is evident with the two experiments from Zhu et al (2015), who attempted to induce mood by having participants read brief news articles that represented intergroup threats, which entailed having participants with low socioeconomic status reading condescending quotes from high socioeconomic individuals. It is not mentioned how long participants spent on these inductions, but both experiments in the study were reported as taking only 10 min to fully complete.…”
Section: Revisiting MCMmentioning
confidence: 79%
“…Hence, these manipulations were perhaps not strong enough to facilitate postencoding biases, nor were they specifically matched to the encoded stimulus set (i.e., the stimuli were not normed to be amusing to match with the comedic clips). A similar concern is evident with the two experiments from Zhu et al (2015), who attempted to induce mood by having participants read brief news articles that represented intergroup threats, which entailed having participants with low socioeconomic status reading condescending quotes from high socioeconomic individuals. It is not mentioned how long participants spent on these inductions, but both experiments in the study were reported as taking only 10 min to fully complete.…”
Section: Revisiting MCMmentioning
confidence: 79%
“…Objective socioeconomic status. Based on previous studies [48][49][50] , the family income for each month, education and occupation for mother and father were used to measure OSES. The 7-piont scale was used to rate the income: 0-600, 601-1800, 1801-3000, 3001-6000, 6001-9000 and 9001-12,000 where the unit of each number was "yuan" for RMB.…”
Section: Subjectsmentioning
confidence: 99%
“…Socioeconomic status (SES) is a measurement of individual’s social and economic status relative to other people in their social hierarchy, which can be divided into objective SES (OSES) and subjective SES (SSES) 19 , 20 . The OSES was the traditional indicators of SES through the evaluation of income, education, and occupation of individuals’ family 21 , 22 , while SSES is used to evaluate “a person’s belief about his location in a status order” 23 and can be seen as perceived social position or subjective social status 24 , 25 . Considering that SSES is the cognitive average of various factors of SES, SSES is more precise evaluation of SES 20 , 26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disorders of GA are involved in a variety of nervous system problems, including melancholic depression, bipolar disorders, attention deficit hyperactivity disorder, sleep problems, and disorders of consciousness (10). In addition, proper modulation of GA is essential for function in multiple cognitive tasks as described by the classical Yerkes-Dodson law (12)(13)(14)(15).…”
mentioning
confidence: 99%